Análise fractal na caracterização de colágenos tipos I e III em feridas dérmicas tratadas com diferentes fontes de plasma rico em plaquetas - MELO, Gabriela Haro de (2017)
Due to its high concentration of growth factors, platelet-rich plasma (PRP) has become the subject of much research, either as an isolated or adjuvant treatment for wound repair. The fractal dimension has been used as an innovative method for the characterization and quantification of tissue structural alterations without any interference from the evaluator. The objective of this study was characterizing collagen types I and III in experimentally induced wounds and treated with different PRP sources by means of fractal dimension and other histological analyzes using blades stained with picrocirius-red and hematoxylin-eosin (HE). In statistical analysis, the variables presented a non-parametric distribution; thus, Mann-Whitney and Kruskall-Wallis tests (p<0,05) were performed using the Student-Newman-Keuls method. It was observed an increase of the collagen fibers by measuring the area with Threshold Color in the different treatments, especially with autologous PRP (p = 0.009) and heterologous PRP (p = 0.016). The fractal dimension of type I collagen had a significant increase for the autologous group (p = 0.028) in relation to the control, but, on average (p <0.05), type III collagen was higher than type I. Fractal dimension was efficient to separately characterize type I and type III collagen fibers. In this study, collagenization was higher in autologous, heterologous and homologous PRP treatments.